Bamboo pulp compound and preparation method thereof, fiber composite material and preparation method and application thereof
By mixing modified bamboo fibers and bamboo slurry under polar solvents, bamboo slurry composites are prepared and hot pressed, the problem of insufficient mechanical properties of traditional bamboo slurry materials is solved, and high-strength and high-tough fiber composites are realized, suitable for special safety helmets, outdoor floors and industrial machine shells.
Patent Information
- Application Number
- CN202510625502.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-12
AI Technical Summary
The prior art is difficult to effectively replace non-degradable petroleum-based plastics, and the mechanical properties of traditional bamboo slurry materials are insufficient, especially the impact toughness is poor.
In the presence of a polar solvent, the bamboo slurry and modified bamboo fibers are mixed and dispersed, the polar solvent is removed to a constant weight, the moisture content is adjusted, and then hot pressing is performed to prepare a bamboo slurry complex. The modified bamboo fibers contain aldehyde and/or carboxy groups, and the aldehyde and/or carboxy groups content is 1-5 mmol/g.
The prepared fiber composite material has excellent mechanical properties, tensile strength not less than 110MPa, flexural strength not less than 100MPa, impact toughness exceeds 15kJ/m2, and has good water resistance and degradability.
Smart Images

Figure BDA0005403815950000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bamboo materials, and in particular to a bamboo pulp composite material and a preparation method thereof, a fiber composite material and a preparation method and application thereof. Background Art
[0002] Global annual plastic production exceeds 400 million tons, of which approximately 30% ends up in natural ecosystems, causing long-term pollution in soil, water, and oceans. The non-degradability of traditional petroleum-based plastics means they can persist in the environment for centuries, gradually breaking down into microplastics (<5mm) that harm human health through the food chain. Against this backdrop, the "Plastic Replacement" initiative aims to replace petroleum-based plastics by developing and utilizing biodegradable, low-carbon bamboo-based materials.
[0003] As a key vehicle for replacing wood and plastic with bamboo, the bamboo pulp industry has been included in key national and local support areas. Bamboo pulp production has increased from 1.75 million tons in 2012 to 2.46 million tons in 2022, and bamboo pulp paper production has reached 2.354 million tons (in 2022), with continued rapid expansion expected. Summary of the Invention
[0004] The purpose of the present invention is a bamboo pulp composite and a preparation method thereof, a fiber composite material and a preparation method and application thereof. The present invention mixes and disperses bamboo pulp and modified bamboo fiber in the presence of a polar solvent, removes the polar solvent to constant weight, and adds water to obtain a bamboo pulp composite with a target moisture content. The bamboo pulp and modified bamboo fiber of the present invention are uniformly dispersed. The fiber composite material prepared from the bamboo pulp composite of the present invention has excellent mechanical properties, especially high impact toughness.
[0005] The inventors of the present invention provide a high-strength, water-resistant, and degradable all-bamboo-based thermosetting plastic in CN202410039251.4. On this basis, the present invention proposes to use bamboo fiber modified with a certain content of aldehyde and / or carboxyl as the matrix phase, and combine it with bamboo pulp fiber as the reinforcing phase to prepare a fiber composite material. The prepared fiber composite material has excellent mechanical properties, especially excellent impact toughness.
[0006] The first aspect of the present invention provides a method for preparing a bamboo pulp composite, which comprises: mixing and dispersing bamboo pulp and modified bamboo fiber in the presence of a polar solvent, removing the polar solvent to constant weight, and adding water to obtain a bamboo pulp composite with a target moisture content, wherein the bamboo pulp content is 1wt%-20wt%, and the modified bamboo fiber content is 80wt%-99wt% based on the total weight of the bamboo pulp and the modified bamboo fiber; the modified bamboo fiber contains aldehyde groups and / or carboxyl groups, and the aldehyde group and / or carboxyl group content is 1-5mmol / g.
[0007] A second aspect of the present invention provides a bamboo pulp composite prepared by the method for preparing the bamboo pulp composite of the present invention.
[0008] A third aspect of the present invention provides a method for preparing a fiber composite material, the method comprising:
[0009] A bamboo pulp composite is prepared according to the preparation method of the bamboo pulp composite of the present invention, the target moisture content of the bamboo pulp composite is adjusted to 30wt%-100wt%, and the bamboo pulp composite is hot pressed until the density is not less than 1.4g / cm 3 .
[0010] A fourth aspect of the present invention provides a fiber composite material prepared by the preparation method of the present invention.
[0011] A fifth aspect of the present invention provides a use of the fiber composite material of the present invention in a special safety helmet, outdoor flooring or industrial machine housing.
[0012] Through the above technical solution, the fiber composite material of the present invention has the following beneficial effects:
[0013] 1. The fiber composite material of the present invention has high mechanical strength, tensile strength not less than 110MPa, flexural strength not less than 100MPa, and impact toughness exceeding 15kJ / m 2 .
[0014] 2. The fiber composite material of the present invention has excellent water resistance. After a 30-day water immersion test, the volume expansion rate is less than 1%.
[0015] 3. The fiber composite material of the present invention has excellent plasticity and can be used to prepare various special-shaped products.
[0016] 4. The fiber composite material of the present invention is biodegradable and chemically degradable, and can be completely degraded within 2 to 3 months after being buried underground, and can also be rapidly degraded (less than 6 hours) in a 1% sodium hydroxide solution. DETAILED DESCRIPTION
[0017] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0018] A first aspect of the present invention provides a method for preparing a bamboo pulp composite, comprising: mixing and dispersing bamboo pulp and modified bamboo fiber in the presence of a polar solvent, removing the polar solvent to a constant weight, and adding water to obtain a bamboo pulp composite having a target moisture content, wherein the bamboo pulp content is 1wt%-20wt% and the modified bamboo fiber content is 80wt%-99wt% based on the total weight of the bamboo pulp and modified bamboo fiber; the modified bamboo fiber contains aldehyde and / or carboxyl groups, and the aldehyde and / or carboxyl group content is 1-5mmol / g. Mixing and dispersing the bamboo pulp and modified bamboo fiber in the presence of a polar solvent achieves uniform composite formation of the bamboo pulp and modified bamboo fiber; the fiber composite material prepared from the bamboo pulp composite of the present invention has excellent mechanical properties, particularly high impact toughness.
[0019] The test standard for carboxyl content in modified bamboo fiber is GB / T 10338-2008. For example, 0.1 g of freeze-dried modified bamboo fiber is placed in a 250 mL conical flask, 10 mL of 0.25 mol / L hydroxylamine hydrochloride (NH2OH·HCl) solution is added, 4 drops of thymol blue indicator are added, and titration is performed with 0.1 mol / L NaOH solution. The endpoint is when the solution turns blue and does not fade within 30 seconds (titration is repeated 3 times in parallel). The carboxyl content is calculated as follows:
[0020] C COOH =C NaOH (V sample -V control ) / (m*1000)*162*100%
[0021] Where:
[0022] C COOH ——Carboxyl (-COOH) content, mmol / g;
[0023] C NaOH ——Concentration of NaOH solution, 0.1 mol / L;
[0024] V sample ——The volume of NaOH solution consumed by DAWF powder, mL;
[0025] V control ——The volume of NaOH solution consumed by the control group, mL;
[0026] m——mass of formaldehyde-treated wood fiber, g;
[0027] 162 – Molecular mass of the cellulose repeating unit, g / mol.
[0028] Aldehyde content: After additional oxidation of the modified bamboo fiber, the aldehyde groups in the modified bamboo fiber are oxidized to carboxyl groups. The carboxyl content of the bamboo powder before and after the additional oxidation is calculated using the above-mentioned carboxyl content test method. The aldehyde content is calculated based on the difference in carboxyl content of the modified bamboo fiber before and after the additional oxidation.
[0029] In the present invention, the additional oxidation step of the modified bamboo fiber includes: mixing bamboo powder with a fixed amount of carboxyl groups with an oxidizing agent for oxidation, wherein the oxidizing agent is a 2 wt % sodium chlorite aqueous solution with a pH of 4-5, and the oxidation time is 24 hours.
[0030] In the present invention, bamboo pulp refers to a fibrous material obtained by separating cellulose from most non-cellulose components such as lignin and hemicellulose in bamboo by chemical or mechanical methods.
[0031] According to a preferred embodiment of the present invention, the content of bamboo pulp in the composite is 5wt%-20wt%, and the content of modified bamboo fiber is 80wt%-95wt%.
[0032] According to a preferred embodiment of the present invention, the content of bamboo pulp in the composite is 5wt%-10wt%, and the content of modified bamboo fiber is 90wt%-95wt%.
[0033] According to a preferred embodiment of the present invention, the bamboo pulp material composition includes: the bamboo pulp material composition includes: cellulose content of 95wt%-99wt%, hemicellulose content of 0-0.5wt%, and lignin content of 0.3wt%-1.5wt%.
[0034] According to a preferred embodiment of the present invention, the modified bamboo fiber material composition includes: a cellulose content of 95wt%-99wt%, a hemicellulose content of 0-0.5wt%, and a lignin content of 0.3wt%-1.5wt%.
[0035] According to a preferred embodiment of the present invention, the target moisture content of the bamboo pulp composite is 30 wt%-100 wt%.
[0036] According to a preferred embodiment of the present invention, the content of aldehyde and / or carboxyl groups in the modified bamboo fiber is 1-3 mmol / g, which is beneficial to improving the mechanical properties of the fiber composite material.
[0037] In the present invention, as long as the modified bamboo fiber contains aldehyde groups and / or carboxyl groups, and the aldehyde groups and / or carboxyl groups content is 1-5 mmol / g, there is no particular limitation on the preparation method of the modified bamboo fiber. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the modified bamboo fiber, comprising: contacting the bamboo fiber with a solution containing an oxidant.
[0038] According to a preferred embodiment of the present invention, the contact conditions include: a contact temperature of 10-80° C., and a contact time of 0.5-50 h.
[0039] According to a preferred embodiment of the present invention, in the solution containing the oxidant, the mass concentration of the oxidant is 0.5%-10%.
[0040] According to a preferred embodiment of the present invention, the oxidant is selected from one or more of periodate 2,2,6,6-tetramethylpiperidinium nitrogen-oxide, nitrogen tetroxide, hypochlorite and oxygen base.
[0041] According to a preferred embodiment of the present invention, the mass ratio of bamboo fiber to oxidant is 1:0.5-5.
[0042] The bamboo fiber may be, for example, the bamboo pulp described in the present invention.
[0043] In the present invention, the amount of polar solvent can be selected in a wide range, as long as the bamboo pulp and modified bamboo fiber can be evenly mixed. According to a preferred embodiment of the present invention, the mass ratio of bamboo pulp and modified bamboo fiber to polar solvent is 1:10-100 based on the total weight of bamboo pulp and modified bamboo fiber.
[0044] In the present invention, bamboo pulp and modified bamboo fiber are dispersed and mixed in a polar solvent, which can achieve uniform compounding of the bamboo pulp and modified bamboo fiber, thereby improving the impact toughness of the fiber composite material. There is no particular limitation on the type of polar solvent. According to a preferred embodiment of the present invention, the polar solvent is selected from one or more of water, C1-C6 small molecule alcohols, dimethyl sulfoxide and DMF, preferably one or more of water, ethanol, methanol and dimethyl sulfoxide, and more preferably water.
[0045] In the present invention, there is no particular limitation on the dispersion method, as long as the bamboo pulp and the modified bamboo fiber are evenly mixed. According to a preferred embodiment of the present invention, the dispersion method is stirring. Preferably, the stirring speed is 300-500 r / min and the stirring time is 4-12 h.
[0046] In the present invention, the polar solvent is removed until the mixture of bamboo pulp and modified bamboo fiber reaches a constant weight. There is no particular limitation on the method of removing the polar solvent. According to a preferred embodiment of the present invention, the polar solvent is removed by one or more of drying and blowing, and the preferred drying temperature is 30°C-60°C. In the embodiment of the present invention, after most of the water is removed by filtration, drying at 40°C is used as an exemplary illustration.
[0047] A second aspect of the present invention provides a bamboo pulp composite prepared by the method for preparing the bamboo pulp composite of the present invention.
[0048] A third aspect of the present invention provides a method for preparing a fiber composite material, the method comprising:
[0049] A bamboo pulp composite is prepared according to the preparation method of the bamboo pulp composite of the present invention, the target moisture content of the bamboo pulp composite is adjusted to 30wt%-100wt%, and the bamboo pulp composite is hot pressed until the density is not less than 1.4g / cm 3 In the present invention, by uniformly compounding bamboo pulp and modified bamboo fiber, controlling the moisture content of the mixture and then performing hot pressing, the fiber composite material can have excellent mechanical properties, especially improved impact toughness.
[0050] In the present invention, the moisture content refers to the percentage of water to the absolute dry mass of solid matter (bamboo pulp and modified bamboo fiber).
[0051] According to a preferred embodiment of the present invention, the heat pressing is performed to a density of 1.4-1.8 g / cm 3 .
[0052] According to a preferred embodiment of the present invention, the density of the fiber composite material prepared by the above preparation method is 1.4-1.8 g / cm 3 .
[0053] The fiber composite material of the present invention has excellent mechanical properties, especially high impact toughness. According to a preferred embodiment of the present invention, the impact toughness of the fiber composite material prepared by the above preparation method is not less than 12 kJ / m 2 , preferably 15-20 kJ / m 2 .
[0054] According to a preferred embodiment of the present invention, the hot pressing conditions include: a temperature of 60-100° C. and a pressure of 20-50 MPa.
[0055] According to a preferred embodiment of the present invention, the preparation method further comprises drying the product after hot pressing, and the drying conditions include: drying temperature of 50-80° C. and drying time of 1-12 hours.
[0056] A fourth aspect of the present invention provides a fiber composite material prepared by the preparation method of the present invention.
[0057] A fifth aspect of the present invention provides an application of the fiber composite material of the present invention in special safety helmets, outdoor floors or industrial machine housings.
[0058] The fiber composite material of the present invention can be used to replace hard plastics (such as polypropylene plastics and polyethylene plastics) by selecting a corresponding mold and performing the hot pressing on the bamboo pulp composite to obtain a corresponding product.
[0059] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0060] In order to more clearly illustrate the present invention, the following examples are given, but the present invention is not limited to the scope of the examples.
[0061] In the following examples, the flexural strength was measured according to the national standard GB / T9341-2008, the tensile strength was measured according to the national standard GB / T1040.2-2006, and the impact toughness was measured according to the national standard GB / T 18743.1-2022.
[0062] The water absorption expansion rate of the samples immersed in water for 10 days and the mass loss rate after burial for 120 days were also measured.
[0063] The standard for determining lignin content is: GB / T 2677.8-1994.
[0064] The standard for determining hemicellulose content is: GBT 2677.9-1994.
[0065] The standard for determining cellulose content is: GBT 744-2004.
[0066] In the following examples, the bamboo pulp 1 has a cellulose content of 99.4 wt %, a hemicellulose content of 0.2 wt %, and a lignin content of 0.4 wt %.
[0067] The bamboo pulp 2 has a cellulose content of 95.3 wt%, a hemicellulose content of 0.5 wt%, and a lignin content of 4.2 wt%.
[0068] Preparation Example 1
[0069] Bamboo pulp 1 was added to a 5% sodium periodate solution and 1% isopropyl alcohol, and the mixture was allowed to react in the dark for 3 hours. The resulting sample was dried at 35°C to a constant weight, yielding a modified bamboo fiber with a total carboxyl and aldehyde content of 3 mmol / g. The modified bamboo fiber contained 99.4% cellulose, 0.2% hemicellulose, and 0.4% lignin.
[0070] Preparation Example 2
[0071] Bamboo pulp 1 was added to a 5% sodium periodate aqueous solution and 1% isopropyl alcohol, and the mixture was allowed to react in a dark environment for 50 minutes. The reacted sample was dried at 35°C to constant weight to obtain a modified bamboo fiber having a total carboxyl and aldehyde group content of 1 mmol / g. The modified bamboo fiber contained 99.4% cellulose, 0.2% hemicellulose, and 0.4% lignin.
[0072] Preparation Example 3
[0073] Bamboo pulp 1 was added to a 5% sodium periodate aqueous solution, followed by 1% isopropyl alcohol, and the mixture was allowed to react in the dark for 8 hours. 1% 2,2,6,6-tetramethylpiperidinium N-oxide was then added and allowed to react for 2 hours. The resulting sample was dried at 35°C to a constant weight, yielding a modified bamboo fiber with a total carboxyl and aldehyde content of 5 mmol / g. The modified bamboo fiber contained 99.4% cellulose, 0.2% hemicellulose, and 0.4% lignin.
[0074] Example 1
[0075] (1) Bamboo pulp 1 (5% by mass) and modified bamboo fiber prepared in Preparation Example 1 (95% by mass) were added to water at a solid mass to water ratio of 1:50, stirred at a speed of 300 r / min for 8 h, filtered to remove most of the water, and dried at 40° C. to obtain a uniform mixture of the two;
[0076] (2) adding water to adjust the moisture content of the mixture to 40%;
[0077] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber composite material was dried at 60°C for 12 hours. The flexural strength, tensile strength, impact strength, water absorption expansion rate and 120-day buried mass loss rate of the fiber composite material were tested. The results are shown in Table 1.
[0078] Example 2
[0079] (1) Bamboo pulp 1 (10% by weight) and modified bamboo fiber prepared in Preparation Example 1 (90% by weight) were added to water at a solid mass to water ratio of 1:50. The mixture was stirred at 300 r / min for 8 h and dried at 40°C to obtain a uniform mixture of the two.
[0080] (2) Water was added to adjust the water content of the mixture to 40%.
[0081] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber composite material was dried at 60° C. for 12 h. The test was carried out according to the method of Example 1. The test results are shown in Table 1.
[0082] Example 3
[0083] The method of Example 1 was followed, except that ethanol was used instead of water in step (1), and the other conditions were the same as those of Example 1. The test results are shown in Table 1.
[0084] Example 4
[0085] (1) Bamboo pulp 2 (20% by mass) and modified bamboo fiber prepared in Preparation Example 2 (80% by mass) were added to water at a solid mass to water ratio of 1:100, stirred at a speed of 500 r / min for 12 h, filtered to remove most of the water, and dried at 60° C. to obtain a uniform mixture of the two;
[0086] (2) adding water to adjust the moisture content of the mixture to 100%;
[0087] (3) The product of step (2) was hot pressed at a temperature of 60°C and a pressure of 50 MPa until the density was 1.4 g / cm 3 , dried at 60°C for 12h, and dried at 60°C for 12h to obtain a fiber composite material. The fiber composite material was tested for its flexural strength, tensile strength, impact strength, water absorption expansion rate, and 120-day buried mass loss rate. The results are shown in Table 1.
[0088] Example 5
[0089] The method of Example 1 was followed, except that in step (1), the modified bamboo fiber prepared in Preparation Example 3 was used instead of the modified bamboo fiber prepared in Preparation Example 1, and the other conditions were the same as in Example 1. The test results are shown in Table 1.
[0090] Comparative Example 1
[0091] The method of Example 1 is different in that, in step (1), 100% modified bamboo fiber is used, specifically:
[0092] (1) Adding the modified bamboo fiber to water at a ratio of 1:50, stirring at a speed of 300 r / min for 8 h, removing most of the water by filtration, and drying at 40°C to obtain a uniform mixture of the two;
[0093] (2) adding water to adjust the moisture content of the mixture to 40%;
[0094] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber material was dried at 60°C for 12 hours. The test was carried out according to the method of Example 1. The test results are shown in Table 1.
[0095] Comparative Example 2
[0096] The bamboo pulp 1 was ground and broken up, and water was added to adjust the moisture content to 40%.
[0097] The aqueous bamboo pulp 1 was hot pressed at a temperature of 100° C. for 10 minutes to obtain a full bamboo pulp molding material.
[0098] Comparative Example 3
[0099] The method of Example 1 is the same, except that in step (1), 60% modified bamboo fiber and 40% bamboo pulp are used, specifically:
[0100] (1) Bamboo pulp accounts for 40% by weight and modified bamboo fiber accounts for 60% by weight, and the bamboo pulp and modified bamboo fiber are added to water at a ratio of 1:50 of solid mass to water, stirred at a speed of 300 r / min for 8 h, and dried at 40°C to obtain a uniform mixture of the two;
[0101] (2) adding water to adjust the moisture content of the mixture to 40%;
[0102] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber composite material was dried at 60° C. for 12 h. The test was carried out according to the method of Example 1. The test results are shown in Table 1.
[0103] Comparative Example 4
[0104] The method of Example 1 is the same, except that no water is added during the mixing process of bamboo pulp and modified bamboo fiber. Specifically:
[0105] (1) Bamboo pulp (5% by weight) and modified bamboo fiber (95% by weight) were stirred at a speed of 300 r / min for 8 h, and dried at 40° C. to obtain a uniform mixture of the two;
[0106] (2) adding water to adjust the moisture content of the mixture to 40%;
[0107] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber composite material was dried at 60°C for 12 hours. The flexural strength, tensile strength, impact strength, water absorption expansion rate and 120-day buried mass loss rate of the fiber composite material were tested. The results are shown in Table 1.
[0108] Comparative Example 5
[0109] The method of Example 1 is followed, except that in step (2), the moisture content is adjusted to 10%, specifically:
[0110] (1) Bamboo pulp accounts for 5% by weight and modified bamboo fiber accounts for 95% by weight, and the bamboo pulp and modified bamboo fiber are added to water at a ratio of 1:50 based on the solid mass to water ratio, stirred at a speed of 300 r / min for 8 h, and dried at 40°C to obtain a uniform mixture of the two;
[0111] (2) adding water to adjust the moisture content of the mixture to 10%;
[0112] (3) The product of step (2) was hot pressed at a temperature of 100°C and a pressure of 30 MPa until the density was 1.55 g / cm 3 The fiber composite material was dried at 60°C for 12 hours. The flexural strength, tensile strength, impact strength, water absorption expansion rate and 120-day buried mass loss rate of the fiber composite material were tested. The results are shown in Table 1.
[0113] Table 1
[0114]
[0115] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for preparing a bamboo pulp composite, characterized in that: The method comprises: mixing and dispersing bamboo pulp and modified bamboo fiber in the presence of a polar solvent, removing the polar solvent until the mixture is constant in weight, and adding water to obtain a bamboo pulp composite with a target moisture content, wherein the bamboo pulp content is 1wt%-20wt% and the modified bamboo fiber content is 80wt%-99wt% based on the total weight of the bamboo pulp and the modified bamboo fiber; and the modified bamboo fiber contains aldehyde groups and / or carboxyl groups, and the aldehyde group and / or carboxyl group content is 1-5mmol / g.
2. The method according to claim 1, wherein The bamboo pulp material composition includes: cellulose content of 95wt%-99wt%, hemicellulose content of 0-0.5wt%, and lignin content of 0.3wt%-1.5wt%; and / or The modified bamboo fiber material composition includes: cellulose content of 95wt%-99wt%, hemicellulose content of 0-0.5wt%, and lignin content of 0.3wt%-1.5wt%; and / or The target moisture content of the bamboo pulp composite is 30wt%-100wt%; and / or In the modified bamboo fiber, the content of aldehyde and / or carboxyl groups is 1-3 mmol / g; and / or The polar solvent is selected from one or more of water, C1-C6 small molecule alcohol, dimethyl sulfoxide and DMF, preferably one or more of water, ethanol, methanol and dimethyl sulfoxide, more preferably water.
3. The method according to claim 1 or 2, wherein: The modified bamboo fiber preparation method comprises: contacting the bamboo fiber with a solution containing an oxidant; Preferably, The contact conditions include: contact temperature of 10-80°C, contact time of 0.5-50h; and / or The oxidant-containing solution has a mass concentration of 0.5% to 10%; and / or The oxidizing agent is selected from one or more of periodate 2,2,6,6-tetramethylpiperidinium nitrogen-oxide, nitrogen tetroxide, hypochlorite and oxygen base; and / or The mass ratio of bamboo fiber to oxidant is 1:0.5-5.
4. The preparation method according to any one of claims 1 to 3, wherein The dispersion method is stirring, preferably, the stirring speed is 300-500 r / min, and the stirring time is 4-12 h; and / or The mass ratio of bamboo pulp and modified bamboo fiber to polar solvent is 1:10-100 based on the total weight of bamboo pulp and modified bamboo fiber; and / or The polar solvent can be removed by one or more of drying and purging, and the preferred drying temperature is 30°C-60°C.
5. The bamboo pulp composite prepared by the method for preparing the bamboo pulp composite according to any one of claims 1 to 4.
6. A method for preparing a fiber composite material, characterized in that: The method includes: A bamboo pulp composite is prepared according to the method for preparing a bamboo pulp composite according to any one of claims 1 to 4, wherein the target moisture content of the bamboo pulp composite is adjusted to 30 wt% to 100 wt%, and the bamboo pulp composite is hot pressed until the density is not less than 1.4 g / cm 3 .
7. The preparation method according to claim 6, wherein Hot pressed to a density of 1.4-1.8g / cm 3 and / or The impact toughness of the fiber composite material is not less than 12kJ / m 2 , preferably 15-20 kJ / m 2 .
8. The preparation method according to claim 5 or 6, wherein Hot pressing conditions include: temperature of 60-100°C and pressure of 20-50 MPa; and / or Preferably, the preparation method further comprises drying the product after hot pressing, and the preferred drying conditions include: a drying temperature of 50-80° C., and / or a drying time of 1-12 h.
9. The fiber composite material prepared by the preparation method according to any one of claims 6 to 8.
10. Use of the fiber composite material according to claim 9 in special safety helmets, outdoor floors or industrial machine housings.
Citation Information
Patent Citations
100% bamboo pulp molded product and preparation method thereof
CN115341402A
All-bamboo-based thermosetting plastic as well as preparation method and application thereof
CN117866453A
Modified bamboo pulp, preparation method and application of modified bamboo pulp in bamboo pulp rolling plate for pulp molding direct pressing process
CN118441501A
All-bamboo-based thermosetting bioplastic as well as preparation method and application thereof
CN120098460A
Method for making a biodegradable fibrous material composition
EP2135893A1